2023
DOI: 10.3390/plants12102028
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Selenium Associated with a Multi-Nutrient Fertilizer in Soybean: Yield, Grain Quality, and Critical Se Threshold

Abstract: Selenium uptake and its content in soybean grains are affected by Se application methods. This study evaluated the impact of Se foliar application combined with a multi-nutrient fertilizer (MNF) on soybean, establishing a Se threshold to better understand the relationship between Se content in grains and yield of two genotypes (58I60 Lança and M5917). Two trials were conducted in a 4 × 2 factorial design: four Se rates (0, 10, 40, 80 g Se ha−1) and two methods of foliar Se application (Se combined or not with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Different approaches of Se biofortification include various methods of Se supply (soil, foliar, or seed soaking) and utilization of different Se chemical forms: selenate (+6), selenite (+4), organic Se derivatives, and Se-nanoparticles (nano-Se) [26]. Regarding selenate use, foliar Se application was the most effective in different agricultural crops [27]. Among Se derivatives, selenates are the most labile forms and selenites the most toxic ones, whereas nano-Se is characterized by low toxicity [2,28].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches of Se biofortification include various methods of Se supply (soil, foliar, or seed soaking) and utilization of different Se chemical forms: selenate (+6), selenite (+4), organic Se derivatives, and Se-nanoparticles (nano-Se) [26]. Regarding selenate use, foliar Se application was the most effective in different agricultural crops [27]. Among Se derivatives, selenates are the most labile forms and selenites the most toxic ones, whereas nano-Se is characterized by low toxicity [2,28].…”
Section: Introductionmentioning
confidence: 99%
“…Within a specific dose range, Se promotes the absorption of iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu) by plants. This phenomenon has been confirmed in wheat [29][30][31], soybeans [1], cabbage [32], tomatoes [33], and lettuce [34]. However, research indicates that Se has inhibitory effects on trace elements [35,36], which may vary depending on the Se forms, doses, application methods, and crop types [37].…”
Section: Introductionmentioning
confidence: 94%
“…Selenium (Se) is an important trace element present in animals and humans, serving as a cofactor for antioxidant enzymes, such as glutathione peroxidase. Its functions include bolstering the immune system, reducing cardiovascular disease, thyroid regulation, detoxification, and anticancer and antiviral effects [1]. Humans primarily acquire Se through their daily diet and/or nutritional supplements [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these authors, the improvements observed in response to Se indicate that it plays a regulatory role in plants under stress by positively influencing both enzymatic and non-enzymatic components of the plant's antioxidative defense system. Selenium can also foster synergistic interactions with other nutrients, all of which contribute to improved resilience against abiotic stresses and overall better plant growth [23,24]. However, the study of the effect of isolated Se applications remains to be clarified under specific conditions as a first step to define its effects on the main crops of interest.…”
Section: Introductionmentioning
confidence: 99%